2015
DOI: 10.1016/j.nbd.2015.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Isoform-level brain expression profiling of the spermidine/spermine N1-Acetyltransferase1 ( SAT1 ) gene in major depression and suicide

Abstract: Low brain expression of the spermidine/spermine N-1 acetyltransferase (SAT1) gene, the rate-limiting enzyme involved in catabolism of polyamines that mediate the polyamine stress response (PSR), has been reported in depressed suicides. However, it is unknown whether this effect is associated with depression or with suicide and whether all or only specific isoforms expressed by SAT1, such as the primary 171 amino acid protein-encoding transcript (SSAT), or an alternative splice variant (SSATX) that is involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 55 publications
2
30
0
Order By: Relevance
“…The first study suggesting a dysregulation of the polyamine system in MDD-suicides showed significant decreases in gene and protein expression of SAT1 in the precentral gyrus (BA4) and cortical frontal lobe areas (BA11 and BA8,9) in both non-depressed suicides and MDD-suicides compared to controls (Sequeira et al, 2006). This finding has been confirmed by our group and several others across brain regions and several population groups (Fiori et al, 2011; Guipponi et al, 2009b; Klempan et al, 2009a; Klempan et al, 2009b; Pantazatos et al, 2015; Sequeira et al, 2007). It was also demonstrated that the rs6526342 SNP, located in the promoter regulatory region of SAT1, had a significant effect on gene expression and that this SNP was associated with suicide in a French-Canadian sample (Sequeira et al, 2006), known to have a founder population effect (Scriver, 2001).…”
supporting
confidence: 88%
“…The first study suggesting a dysregulation of the polyamine system in MDD-suicides showed significant decreases in gene and protein expression of SAT1 in the precentral gyrus (BA4) and cortical frontal lobe areas (BA11 and BA8,9) in both non-depressed suicides and MDD-suicides compared to controls (Sequeira et al, 2006). This finding has been confirmed by our group and several others across brain regions and several population groups (Fiori et al, 2011; Guipponi et al, 2009b; Klempan et al, 2009a; Klempan et al, 2009b; Pantazatos et al, 2015; Sequeira et al, 2007). It was also demonstrated that the rs6526342 SNP, located in the promoter regulatory region of SAT1, had a significant effect on gene expression and that this SNP was associated with suicide in a French-Canadian sample (Sequeira et al, 2006), known to have a founder population effect (Scriver, 2001).…”
supporting
confidence: 88%
“…Procedures for brain collection and psychological autopsy, psychiatric diagnosis, inclusion and exclusion criteria are as described above for the genotyped postmortem sample. Postmortem intervals (PMI), RIN scores, and pH for the postmortem samples were within acceptable ranges and are reported elsewhere [Galfalvy et al, 2015; Pantazatos et al, 2015]. …”
Section: Methodsmentioning
confidence: 87%
“…For a detailed description of the RNA-seq methodology as previously described [Pantazatos et al, 2015]. Briefly, RNA was extracted from dorsal prefrontal cortex (BA9) using previously established protocols [Sibille et al, 2004] and conducted according to NIH Roadmap Epigenomics Mapping Consortium (REMC) guidelines.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the RNA sequencing methodology have been previously reported 40 . Briefly, RNA was extracted from dorsal prefrontal cortex (BA9) using previously established protocols 33 and conducted according to the guidelines recommended by the NIH Roadmap Epigenomics Mapping Consortium (REMC).…”
Section: Methodsmentioning
confidence: 99%